UPAYA MENINGKATKAN KEMAMPUAN SISWA KELAS V DALAM MEMAHAMI BACAAN MELALUI TEKNIK SQ3R (SURVEY, QUESTION, READ, RECITE, REVIEW) (Studi Kasus: Kelas V Semester 2 di SD Negeri 2 Tribungan Kecamatan Mangaran Tahun Ajaran 2013-2014) - Nur Jamilah; Hasan Muchtar Fauzi (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Abdurachman Saleh Situbondo, 2015)
This study aims to describe the application of SQ3R (Survey, Question, Read, Recall, Review) techniques to improve the ability of grade V students to understand the reading in SDN 2 Tribungan sub-district of Mangaran, academic year 2013-2014 and to know the improvement of students' learning outcomes after the application of SQ3R technique (Survey, Question, Read, Recall, Review) in reading comprehension. This research wasclassroom action research which was conducted in two cycles, each of the cycle wascovering the planning, implementation, observation and reflection phase. The results showed that the application of reading comprehension through SQ3R technique (Survey, Question, Read, Recall, Review) can improve ability of grade V students in comprehending reading content.